How to Reduce Action Space for Planning Domains? (Student Abstract) - Kokel, Harsha; Lee, Junkyu; Katz, Michael; Sohrabi, Shirin; Srinivas, Kavitha (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
While AI planning and Reinforcement Learning (RL) solve sequential decision-making problems, they are based on different formalisms, which leads to a significant difference in their action spaces. When solving planning problems using RL algorithms, we have observed that a naive translation of the planning action space incurs severe degradation in sample complexity. In practice, those action spaces are often engineered manually in a domain-specific manner. In this abstract, we present a method that reduces the parameters of operators in AI planning domains by introducing a parameter seed set problem and casting it as a classical planning task. Our experiment shows that our proposed method significantly reduces the number of actions in the RL environments originating from AI planning domains.